Impacts of energy efficiency retrofitting measures on indoor PM2.5 concentrations across different income groups in England: a modelling study. Issue 1 (2nd January 2016) - Shrubsole, C.; Taylor, J.; Das, P.; Hamilton, I. G.; Oikonomou, E.; Davies, M.
Abstract : As part of an effort to reduce carbon emissions in the UK, policies encouraging the energy-efficient retrofit of domestic properties are being implemented. Typical retrofits, including installation of insulation and double glazing can cause tightening of the building envelope which may affect indoor air quality (IAQ) impacting occupant health. Using the example of PM2.5 (an airborne pollutant with known health impacts), this study considers the influence of energy-efficient retrofits on indoor PM2.5 concentrations in domestic properties both above and below the low-income threshold (LIT) for a range of tenancies across England. Simulations using EnergyPlus and its integrated Generic Contaminant model are employed to predict indoor PM2.5 exposures from both indoor and outdoor sources in building archetypes representative of (i) the existing housing stock and (ii) a retrofitted English housing stock. The exposures of occupants for buildings occupied by groups above and below the LIT are then estimated under current conditions and following retrofits. One-way ANOVA tests were applied to clarify results and investigate differences between the various income and tenure groups. Results indicate that all tenures below the LIT experience greater indoor PM2.5 concentrations than those above, suggesting possible social inequalities driven by housing, leading to consequences for health.